Pbrm1 intrinsically controls the development and effector differentiation of iNKT cells. Issue 15 (29th June 2022) - Wang, Xin; Lei, Lei; Su, Yanhong; Liu, Jun; Yuan, Ning; Gao, Yang; Yang, Xiaofeng; Sun, Chenming; Ning, Bin; Zhang, Baojun
Abstract: Under static condition, the pool size of peripheral invariant natural killer T (iNKT) cells is determined by their homeostatic proliferation, survival and thymic input. However, the underlying mechanism is not fully understood. In the present study, we found that the percentage and number of iNKT cells were significantly reduced in the spleen, but not in the thymus of mice with deletion of polybromo‐1 (Pbrm1) compared to wild type (WT) mice. Pbrm1 deletion did not affect iNKT cell proliferation and survival, instead significantly impaired their development from stage 1 to stage 2. Importantly, loss of Pbrm1 led to a dysfunction of RORγt expression and iNKT17 cell differentiation, but not iNKT1 and iNKT2 proportion. Collectively, our study reveals a novel mechanism of Pbrm1 controlling the peripheral size of iNKT cells through regulating their development and differentiation.